More risk - less solidarity? An experimental investigation - Jano Costard (European University Viadrina, Department of Business Administration and Economics, 2009)
A solidarity game was conducted where participants were able to choose between two lotteries with same expected values. However, in one lottery, the risky one, participants faced a higher probability to receive no endowment. The winners were then able to discriminate between subjects risk attitude when it came to voluntary transfers from winners to losers in randomly formed three person groups. The results indicated that risk takers were not fully held responsible for their self-inflicted neediness, although they received on average fewer transfers than non-risk-takers. In fact, group favoritism is observed, where non-risk-takers transferred more to loosing non-risk-takers and risk-takers transferred more to loosing risk-takers. This behavioral pattern was stable across different versions of group compounding, profession and gender. Nevertheless, a gender effect was found with regard to lottery choice and the amount of money transferred. Furthermore, similarities can be seen between the results of the experiment and certain aspects of the current financial crisis. Among them borrowing in non-recourse states in the USA, the role of rating agencies and the hiring of failed CEOs.
Is replaced by the following version: http://hdl.handle.net/10419/44354
Keywords: 330; Risikopräferenz; Glücksspiel; Solidarität; Soziale Gruppe; Spieltheorie; Test